2012
DOI: 10.1245/s10434-012-2680-0
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Forkhead Box M1 Transcription Factor (FOXM1) is a Potential Prognostic Marker and Enhances Chemoresistance for Docetaxel in Gastric Cancer

Abstract: Our study showed that FoxM1 was an independent prognostic factor in gastric cancer. Furthermore, we showed that FoxM1 was a critical molecule for chemoresistance to a microtubule-stabilizing anticancer agent, docetaxel. Taken together, those results suggest that inhibition of overexpressed FoxM1 will be a promising therapeutic strategy for advanced gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 29 publications
8
59
1
Order By: Relevance
“…Conversely, silencing of NPM expression sensitized hepatoma cells to doxorubicin, cisplatin, lapatinib, sorafenib and UV-B (16); thus suggesting that the inhibition of NPM may be considered a novel therapeutic strategy for cancer treatment. Human epidermal growth factor receptor-2 (Her-2) is a member of the epidermal growth factor receptor family of receptor tyrosine kinases, which have vital roles in the development and progression of various solid tumors, including gastric cancer (17). Since the downregulation of Her-2 was shown to promote the apoptosis of tumor cells (18), Her-2 is regarded as a potential target in breast and gastric cancer therapy.…”
Section: Downregulation Of Npm Expression By Her-2 Reduces Resistancementioning
confidence: 99%
“…Conversely, silencing of NPM expression sensitized hepatoma cells to doxorubicin, cisplatin, lapatinib, sorafenib and UV-B (16); thus suggesting that the inhibition of NPM may be considered a novel therapeutic strategy for cancer treatment. Human epidermal growth factor receptor-2 (Her-2) is a member of the epidermal growth factor receptor family of receptor tyrosine kinases, which have vital roles in the development and progression of various solid tumors, including gastric cancer (17). Since the downregulation of Her-2 was shown to promote the apoptosis of tumor cells (18), Her-2 is regarded as a potential target in breast and gastric cancer therapy.…”
Section: Downregulation Of Npm Expression By Her-2 Reduces Resistancementioning
confidence: 99%
“…Cellular proteins: Serum level of alpha-1-microglobulin/bikunin precursor (AMBP) protein, as well as increased expression of β-tubulin III protein, was demonstrated to predict lower chemotherapeutic response to paclitaxel-capecitabine schemes [91,92]; regenerating gene family member 4 (Reg IV or REG4) predicted resistance to 5-FU-based regimens [93]; forkhead box M1 (FOXM1) transcription factor seems to predict resistance to docetaxel [94]; and dysregulated ribosomal proteins were found to enhance vincristine, adriamycin, and 5-FU resistance [95].…”
Section: Protein Markersmentioning
confidence: 99%
“…We summarized the eligible studies that focused on the FoxM1 expression and prognosis by cox regression, the details of which were listed in Table 2 (Bektas et al, 2008;Li et al, 2009;Yang et al, 2009;Jiang et al, 2011;Priller et al, 2011;Sun et al, 2011a;2011b;Yu et al, 2011;Chu et al, 2012;He et al, 2012;Xia et al, 2012a;2012b;Xue et al, 2012;Li et al, 2013a;2013b;Okada et al, 2013;Wang et al, 2013a;2013b;Wu et al, 2013;Xu et al, 2013). Studies were eligible if they reported a risk estimate [e.g., hazard ratio (HR) or relative risk (RR) relating FoxM1 expression to subsequent death using survival analysis regression models], and they reported an estimate of precision, such as a standard error or 95%CI.…”
Section: Correlation Between Foxm1 Expression and Clinicopathologicalmentioning
confidence: 99%